Resíduo úmido de fecularia de milho na alimentação de bovinos leiteiros - Anschau, Fernando Andre (2019)
In the ruminants production, the search for cost reductions is common and the use of agroindustrial by-products in feeding is an alternative considering the ruminal fermentation capacity of these animals. Among the many co-products that can be used, the corn starch wet residue (CSWR) is one of them. Two experiments were carried out to evaluate the effect of the inclusion levels of CSWR on the performance of lactating holstein cows and also with fistulated steers. In the first study, five lactating holstein cows were used, distributed in a 5x5 latin square design, fed diets containing 0%, 7.5%, 15%, 22.5% and 30% of CSWR. The periods consisted of 14 days for adaptation and 6 days for collection. The use of CSWR inclusion levels in the diet of holstein cows resulted in a linear effect on the reduction of dry matter and non-fibrous carbohydrate intake and linearly increasing the neutral detergent fiber intake. Dry matter and nutrient digestibility, microbial protein synthesis, blood parameters together with milk yield and composition had no effect due to inclusion of CSWR in the diet. Thus, when the economic assessment was performed, the inclusion of 30% of CFWR presented the best average gross margin and the lowest break-even point. In the second study, five fistulated dairy cattle were used and distributed in a 5x5 latin square experimental design with different inclusion levels 0%, 7.5%, 15%, 22.5% and 30% of CSWR. The periods consisted of 14 days for adaptation and 6 days for collection. The intake and digestibility of dry matter and nutrients and ruminal fermentation parameters were evaluated. Dry matter intakes were not changed, however for crude protein, ether extract, neutral detergent fiber, acid detergent fiber intakes there was a linear increase and a linear decrease in non-fibrous carbohydrate intake due to the levels of CSWR in the diet. The dry matter digestibility and its nutrients were not altered. The ruminal parameters (pH and N-NH3) had no effect with the inclusion of CSWR, however they had a quadratic effect in relation to time after feeding. The use of corn fecular wet residue at inclusion levels of up to 30% reduced total VFA production, but did not alter nutrient intake and digestibility, ruminal pH and ammoniacal nitrogen concentration, and could be used in the feeding of dairy cattle.